2014
DOI: 10.1136/jclinpath-2014-202224
|View full text |Cite
|
Sign up to set email alerts
|

A critical assessment of two real-time PCR assays targeting the (SSU) rRNA and gdh genes for the molecular identification ofGiardia intestinalisin a clinical laboratory

Abstract: The Verweij real-time PCR was robust and the most sensitive assay suited for use as a first-line diagnostic test for giardiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
16
1
Order By: Relevance
“…This makes PCR a more convenient method, as a single sample suffices and thus there is no longer a need for collecting stool samples on three consecutive days in order to reach a diagnostic sensitivity similar to microscopy. Also, because PCR detection does not rely on the detection of intact cysts or motile trophozoites, sensitive detection can still be achieved without the need of preservatives and/or different staining methods …”
Section: New Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This makes PCR a more convenient method, as a single sample suffices and thus there is no longer a need for collecting stool samples on three consecutive days in order to reach a diagnostic sensitivity similar to microscopy. Also, because PCR detection does not rely on the detection of intact cysts or motile trophozoites, sensitive detection can still be achieved without the need of preservatives and/or different staining methods …”
Section: New Detection Methodsmentioning
confidence: 99%
“…Therefore, microscopy requires the availability of highly trained personnel and is very labor intensive . Failures to find and differentiate protozoa by microscope lead to decreased sensitivity that may result in an inadequate diagnosis of intestinal protozoa using microscopy . Even between European reference laboratories, substantial differences were found in detection rates and thus diagnosis of intestinal protozoa using microscopy .…”
Section: Traditional Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the real-time PCR on G. intestinalis, Bertrand et al showed that for an initial concentration of 180 cysts per 200 μl of preparation, only 33% of positive responses were observed [38,39]. Indeed, a relatively low sensitivity (93.4%) was observed by targeting sequences of the small subunit gene of rRNA [40] as in our study.…”
Section: Discussionmentioning
confidence: 41%